Detection of AtRKD4 Gene and Induction of Somatic Embryo in Transformant of Phalaenopsis amabilis Carrying 35S::GR::AtRKD4 - Dika Sundari; Naufal Ghozi Aditya Perdana; Windi Mose; Jose Gutierrez -Marcos; Endang Semiarti (Universitas Gadjah Mada, 2023)
Phalaenopsis amabilis (L.) Blume is a native Indonesian orchid that plays an important role in the breeding of orchid’s hybrid worldwide. The high consumer demand causes a decline in the population of orchids for commercial trade. Plant propagation through induction of somatic embryogenesis will be very beneficial, because plants can be obtained in large numbers and uniform. AtRKD4 gene is an important gene in the model plant Arabidopsis thaliana which functions very early in development stage to initiate embryo formation. The AtRKD4 gene has been inserted into the P. amabilis orchid and several transformants have been obtained. This study aims to determine the stability integration of the AtRKD4 gene in the transformant P. amabilis genome and induce somatic embryo formation on transformant orchids. Plantation of leaf explants from P. amabilis transformants on hormone-free New Phalaenopsis basic medium induced somatic embryo formation by 20%. Anatomical analysis showed that there is no difference stage between anatomy of somatic embryo development pattern in P. amabilis transformant and somatic embryo development pattern of monocot plants in general, PCR analysis using AtRKD4 specific primers showed that the embryos still contained 198 bp fragments of the AtRKD4 gene. In conclusion, the AtRKD4 gene is stably integrated in the P. amabilis orchid genome and can continuously induce the formation of somatic embryo from somatic cells of orchid transformants.